IMPORT SUBSTITUTION STRATEGIES ON THE BUILDING MATERIALS MARKET OF UKRAINE - Romanenko, Olesia; Alaverdian, Liudmyla (SWorld-Ger Conference proceedings, 2023)
The study is devoted to the study of import substitution strategies in the domestic market of construction materials of Ukraine. An analysis of the current state of the construction materials market was carried out, the most critical segments of import de